Sosialisasi Literasi Ekonomi Syariah Bagi Masyarakat di Desa Tanjungsari Kecamatan Pondoksalam Purwakarta - Saepudin, Ahmad (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The majority of rural communities at this time, according to the identity of the population data of Tanjungsari Village, are more dominated by Muslims, so all activities carried out on a daily basis should be in accordance with sharia. Seeing that there are still many community economic activities in Tanjungsari Village, Pondoksalam District, Purwakarta Regency which are not based on knowledge of sharia economics, in which some of them still carry out activities in ribawi, gharar and maisyir transactions and other transactions. So with this dedication it is considered important enough to socialize sharia economic literacy in the people of Tanjungsari Village, Pondoksalam District, Purwakarta Regency. This PKM program aims to provide an understanding of the Islamic economy for the community in Tanjungsari Village, Pondoksalam District, Purwakarta. This PKM method uses a lecture and discussion approach. PKM results on the socialization of "Sharia Economic Literacy" in Tanjungsari Village, Pondoksalam District, Purwakarta Regency "Alhamdulillah it went well, well and smoothly, it can be seen that the participants who took part were very focused on enjoying and listening to this socialization event carefully, besides that the community also felt helped by there are activities to socialize sharia economic literacy in solving problems in economic activity transaction contracts, which according to him so far these daily activities are not in accordance with sharia. The response from the people of Tanjungsari Village was very good, although some people felt they already understood, this outreach activity was far more relevant to the discussion of the problems of daily economic activities originating from the Koran, Hadith, Ijma and Qiyas and explained through examples. his life. Finally, there are people who want to deepen their understanding of Islamic economic literacy.